2009
DOI: 10.1007/s00423-009-0573-x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of thymidylate synthase determines the response of gastric cancer patients undergoing gastrectomy to 5-fluorouracil-based adjuvant chemotherapy

Abstract: Low TS expression is significantly associated with female GC patients and responders to 5-FU-based adjuvant chemotherapy. It predicts longer DFS and OS in selected GC patients treated with 5-FU-based adjuvant chemotherapy after curative resection. The results suggest that prospective assessment of TS staining intensity in tissue samples obtained from GC patients undergoing gastrectomy would be useful to predict the patients who would be benefited from 5-FU-based adjuvant chemotherapy after gastrectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
0
9
2
Order By: Relevance
“…A large number of studies on gastrointestinal and other cancers treated with 5‐FU‐based chemotherapy have demonstrated that high TS and high DPD intratumoral expressions are associated with 5‐FU resistance. High TS expression has been reported to be associated with poor prognosis in colon and gastric cancer patients treated with 5‐FU‐based chemotherapy [35, 36], although the role of TS expression in pancreatic cancer is controversial [19, 37]. Interestingly, Komori et al [21] recently revealed that high TS expression was correlated with gemcitabine resistance and poor RFS in pancreatic cancer patients with resection who were treated with adjuvant gemcitabine therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies on gastrointestinal and other cancers treated with 5‐FU‐based chemotherapy have demonstrated that high TS and high DPD intratumoral expressions are associated with 5‐FU resistance. High TS expression has been reported to be associated with poor prognosis in colon and gastric cancer patients treated with 5‐FU‐based chemotherapy [35, 36], although the role of TS expression in pancreatic cancer is controversial [19, 37]. Interestingly, Komori et al [21] recently revealed that high TS expression was correlated with gemcitabine resistance and poor RFS in pancreatic cancer patients with resection who were treated with adjuvant gemcitabine therapy.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to compare the level of expression seen with other values reported in the literature because of the variety of approaches used to determine positivity. TS expression was reported in 56% (64/114, semiquantitative) of oesophageal adenocarcinoma [13]; 66% (82/124, ≥20% cytoplasmic immunostaining taken as positive) of stomach cancers [16]; and 61% (19/31, same method as used here) of oesophageal adenocarcinoma [20]. In colorectal cancers, positive TS expression was seen in 72% (Grades 2, 3 versus 0, 1) [22] and 70% (semiquantitative, 0–2/3-4) [23] of patients.…”
Section: Discussionmentioning
confidence: 99%
“…In gastric cancer TS expression has been studied as a predictive marker of response to chemotherapy [1416] and poor differentiation [17]. Patients in the United Kingdom with operable gastric and gastro-oesophageal junction (GOJ) tumours receive neoadjuvant chemotherapy prior to surgical resection according to the United Kingdom Medical Research Council Adjuvant Gastric Infusional Chemotherapy protocol [7].…”
Section: Introductionmentioning
confidence: 99%
“…In three studies (Boku et al, 1998;Yeh et al, 1998;Miyamoto et al, 2000), staining intensity grades lower than 1 or 2 represented low levels of TS expression. In five studies (Choi et al, 2001;Tahara et al, 2004;Boku et al, 2007;Lee et al, 2008;Yeh et al, 2010), expression was dichotomized by quantifying the proportion of stained cells using arbitrary thresholds of 20% or 25%. In two studies (Kwon HC et al, 2007;Kim KH et al, 2011), cases were defined as high expression on the condition that the grades of intensity and extent are both 2 or higher.…”
Section: Evaluation Of Ts Methodologiesmentioning
confidence: 99%
“…In the study by Boku et al (Boku et al, 2007), ORR data were presented separately for patients who received 5-fluorouracil (5-FU) or 5-FU/ Cisplatin, therefore two patient cohorts were considered separately for pooling. In the adjuvant disease setting, nine studies that included survival data of total 1,235 patients available for pooling (median: 103, range: 39-463) were eligible (Suda et al, 1999;Choi et al, 2001;Cho et al, 2006;Hua et al, 2007;Lee et al, 2008;Ishido et al, 2009;Kim et al, 2009;Yeh et al, 2010;Kim et al, 2011). Adjuvant fluoropyrimidine chemotherapy was given postoperatively to all patients.…”
Section: Eligible Studies and Characteristicsmentioning
confidence: 99%